2010
DOI: 10.1051/0004-6361/201014538
|View full text |Cite
|
Sign up to set email alerts
|

The 3-D structure of SN 1987A's inner ejecta

Abstract: Context. Observing the inner ejecta of a supernova is possible only in a handful of nearby supernova remnants. The core-collapse explosion mechanism has been extensively explored in recent models and predict large asymmetries. SN 1987A is the first modern stellar explosion that has been continuously observed from its beginning to the supernova remnant phase. Twenty years after the explosion, we are now able to observe the three-dimensional spatially resolved inner ejecta of this supernova. Aims. Detailed mappi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…As mentioned in Section 1, the 3D morphology of the inner ejecta of SN 1987A is globally elliptical/elongated (Kjaer et al 2010;Larsson et al 2013Larsson et al , 2016. The distributions of the observed [Fe II] lines in the Doppler velocity are biased toward the redshifted side.…”
Section: Morphology Of the Supernova Ejecta And The Explosion Mechanimentioning
confidence: 70%
See 2 more Smart Citations
“…As mentioned in Section 1, the 3D morphology of the inner ejecta of SN 1987A is globally elliptical/elongated (Kjaer et al 2010;Larsson et al 2013Larsson et al , 2016. The distributions of the observed [Fe II] lines in the Doppler velocity are biased toward the redshifted side.…”
Section: Morphology Of the Supernova Ejecta And The Explosion Mechanimentioning
confidence: 70%
“…In this paper, we assume the form of the initial radial velocities as v r ∝ r f (θ). Since observations of SN 1987A have shown that the inner ejecta is globally elliptical (Kjaer et al 2010;Larsson et al 2013Larsson et al , 2016, bipolar-like explosions may be justified. Then, the following four cases for the shape of f (θ) (0 ≤ θ ≤ π) are considered.…”
Section: A Explosion Asymmetries: Initial Radial Velocity Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distances between the SN and the centers of the NOR and SOR were set to 1.3 and 1.0 × 10 18 cm, respectively, consistent with the range of distances to the ORs reported by Tziamtzis et al (2011). We also apply a small rotation of the system around the north-south axis in order to match the 7 • tilt of the major axis of the ER (obtained from the fits in Section 6, see also Kjaer et al 2010) and the similar observed tilts of the ORs. Finally, we shift the centers of the NOR and SOR to the west by 5.5 and 4.0 × 10 16 cm, respectively, which results in a good agreement between the projected model and the images.…”
Section: The Diffuse Emissionmentioning
confidence: 99%
“…The fact that molecules and dust are observed in the inner ejecta also shows that these regions are not significantly affected by the X-rays (Matsuura et al 2015;Fransson et al 2016;Abellán et al 2017;Larsson et al 2019;Cigan et al 2019). The 3D emissivities of a number of atomic and molecular emission lines from the ejecta have been determined using a combination of imaging and spectra, revealing a highly asymmetric distribution (Kjaer et al 2010;Larsson et al 2013Larsson et al , 2016Abellán et al 2017;Larsson et al 2019). Several different early observations also provided strong evidence for an asym- metric explosion, including polarimetry (Schwarz 1987;Jeffery 1991), the "mystery spots" (Nisenson et al 1987;Meikle et al 1987;Nisenson & Papaliolios 1999) and the "Bochum event" (Hanuschik & Thimm 1990).…”
Section: Introductionmentioning
confidence: 99%